Corporate Social Responsibility and Firm Value: Mediating Earnings Management - Andriyanti, Vesha Dillah; Aulia, Yoosita (Akuisisi : Jurnal Akuntansi, 2024)
This study aims knowing the impact of corporate social responsibility (CSR) on firm value with earnings management as mediating variable. The objects of this study are 12 companies in Indonesia from energy sector that listed on the Indonesia Stock Exchange (IDX) which were selected as research samples with the research study period 2019-2022. The analytical tools used in this research are regression and pathy analysis. The results of this study indicate that corporate social responsibility has no effect on earnings management. Corporate social responsibility affects firm value, earning managements affects firm value. Corporate social responsibility and earning management affect firm value but earnings management has not been able to mediate the influence of corporate social responsibility on firm value.